2019
DOI: 10.20944/preprints201910.0185.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sodium and Potassium Intakes and Cardiovascular Risk Profiles in Childhood Cancer Survivors: The SCCSS-Nutrition Study

Abstract: Risk of cardiovascular disease (CVD), common in childhood cancer survivors (CCSs), may be affected by diet. We assessed sodium (Na) and potassium (K) intake, estimated from food frequency questionnaires (FFQs) and morning urine spots, and its associations with cardiovascular risk in CCSs. We stratified CCS into three risk profiles based on A) personal history (CVD, CVD risk factors, or CVD risk free), B) body mass index (obese, overweight, or normal/underweight), and C) cardiotoxic treatment (anthracyclines an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…26 Problems with either 24-hour or weekly dietary recalls include the error in reporting due to misreporting, 27 biased reporting of foods consumed, 28 or significant variation in day-to-day food intake, 29 all of which can reduce the accuracy of these recall methods. For example, some studies have reported accurate sodium and inaccurate potassium intake 30 whereas others have presented the opposite; inaccurate sodium and accurate potassium intake. 31 Though less prone to user bias, 24-hour urinary sodium excretion measures as an indicator of nutrient intake may also have limited accuracy.…”
Section: Improving Measures Of Electrolyte Intakementioning
confidence: 99%
“…26 Problems with either 24-hour or weekly dietary recalls include the error in reporting due to misreporting, 27 biased reporting of foods consumed, 28 or significant variation in day-to-day food intake, 29 all of which can reduce the accuracy of these recall methods. For example, some studies have reported accurate sodium and inaccurate potassium intake 30 whereas others have presented the opposite; inaccurate sodium and accurate potassium intake. 31 Though less prone to user bias, 24-hour urinary sodium excretion measures as an indicator of nutrient intake may also have limited accuracy.…”
Section: Improving Measures Of Electrolyte Intakementioning
confidence: 99%